Sustainable Accounting in the ESG Era: A Literature Review on the Integration of Environmental, Social, and Governance Aspects in Financial Reporting - Nopi Handayani (Count : Journal of Accounting, Business and Management, 2025)
This study aims to examine how Environmental, Social, and Governance (ESG) factors are integrated into financial reporting practices, particularly within the context of emerging economies. In contrast to traditional financial accounting, sustainable accounting seeks to incorporate ESG dimensions to provide a more holistic view of organizational performance. Using a qualitative research approach, this study employs a structured literature review method to analyze journal articles, regulatory reports, and international ESG disclosure standards published over the last decade. The findings indicate that while ESG integration is gaining global traction, its application remains inconsistent across jurisdictions due to regulatory disparities, voluntary adoption, and varying interpretations of ESG metrics. Moreover, the study highlights that environmental indicators dominate ESG reporting, while governance and social dimensions are often underrepresented. A key novelty of this research lies in its focus on the practical barriers to ESG implementation in developing markets, offering insights into how local institutions respond to global sustainability demands. The study also contributes methodologically by combining regulatory analysis with thematic content review to generate generalizable patterns. In conclusion, although ESG reporting frameworks are expanding, their adoption and effectiveness vary widely. This research suggests the urgent need for standardized ESG guidelines that are adaptable to local contexts while still aligned with global standards. By emphasizing both policy and practice, this study contributes to the advancement of sustainable accounting and supports ongoing global efforts toward responsible corporate disclosure.